FORMULATION AND EVALUATION OF TRANSDERMAL PATCHES OF PSEUDOEPHEDRINE HCL - SAMIULLAH; JAN, SYED UMER; GUL, RAHMAN; JALALUDIN, SYED; ASMATHULLAH (International Journal of Applied Pharmaceutics, 2020)
Objective: This study was conducted to design a transdermal dosage form of pseudoephedrine HCL and to evaluate its release under controlled rates for sustained transdermal delivery of Pseudoephedrine. Methods: Transdermal patches were prepared by the casting evaporation method. Utilizing eudragit RL100. Patches were characterized by physical appearance, moisture content, thickness, weight variation, folding endurance, tensile strength and stability studies. Fourier transform infrared spectroscopic studies (FTIR), differential scanning calorimetry analysis (SCA) and XRD studies. Four different permeation enhancer (Tween 20, thymus oil, castor oil and eucalyptus oil) was employed. In vitro release of drugs was done in the dissolution paddle apparatus. Release studies were performed in distilled water at 37 °C. Scanning electron microscope studies were performed before and after the drug. Results: Transdermal patches with enhancers were formulated successfully with a concentration of 1% (W/V). The patches indicated stable physicochemical characteristics. FTIR, SCA and XRD Studies showed that there were no physical and chemical interactions between excipients and drugs. Results of in vitro permeation studies showed that enhancers used in this study increased drug released. The enhancers showed faster released than no enhancer. This arrangement can be shown as Tween>Eucalyptus oil>Thymus oil and castor oil. Formulation F2 is optimized among all formulations showed an 83.3% release. Conclusion: Transdermal patches of pseudoephedrine were successfully developed by using pseudo epinephrine HCL. These patches proved to be very useful for therapeutic purposes in the pharmaceutical industry without making the patients unconscious, unlike the trivial methods of treatment.